The United Nations' (UN) decision to adopt International Public Sector Accounting Standards (IPSAS). Issue 2 (3rd June 2019) - Chow, Danny; Aggestam Pontoppidan, Caroline
Abstract : Purpose: The purpose of this paper is to analyse and understand the UN System's adoption of IPSAS from a legitimacy perspective. Design/methodology/approach: A content analysis of publicly accessible documents from the UN System archives was conducted. The analysis was framed through the broader lens of legitimacy theory, drawing attention to the rationalities of decisions taken. Findings: This study illustrated how the need for accounting reforms was rationalised throughout the UN System of organisations. Decision-making processes were reflective of political concerns and the accompanying need to continually demonstrate accountability. The discursive strategies observed associated the need to improve accountability with the adoption of globally recognised accounting systems. However, such logic assumed that existing accountability deficits were intrinsically linked to accounting failures, which overemphasises accounting's role. Social implications: The UN System's decision to adopt IPSAS in 2006 has been followed by a substantial increase in the number of Member States following suit. However, governments and other organisations considering IPSAS adoption should be aware of the historical context in which the UN System's decision was made. Originality/value: This study addresses a lacuna in empirical studies providing an understanding of the role of accounting reforms within international organisations such as the UN System.